Sosialisasi Kampanye “GEMARIKAN” (Gerakan Memasyarakatkan Makan Ikan) Melalui Produk Olahan Ikan Untuk Peningkatan Gizi Anak-anak di SDN Alue Peunyareng (ALPEN), Kecamatan Meureubo, Kabupaten Aceh Barat - Insani, Sri Ayu; Khairi, Ikhsanul; Hasanah, Uswatun; Diansyah, Akbar; Rozi, Anhar; Ukhty, Nabila (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2024)
Protein from fish is needed by the human body because it is relatively easy to digest. Policies to support the availability of marine resources as a source of animal protein play an important role in improving diets so as to prevent disruption of children's growth. Children are the forerunners of the nation's next generation. The formation of children's qualities since school will influence the quality of Human Resources (HR) when they reach productive age. School-aged children are a group that requires attention when consuming food and nutrients. Optimal growth and development of school-aged children depends on providing nutrition with good quality and quantity. The level of fish consumption in fishing families is influenced by several things, namely income, number of family members, perception of the price of fish, tastes, and also the level of education, or perhaps also the level of knowledge regarding the benefits of consuming fish. It is hoped that various types of interesting processed fish products can increase fish consumption patterns in the community, especially among children who are growing up. On this basis, it is necessary to hold a GEMARIKAN campaign (Movement to Promote Fish Eating) in schools, especially elementary schools. This activity aims to provide education about the benefits of consuming fish, and shift snacks to processed fish products, which are healthy and beneficial for children's growth and development.